Policy transfer and lesson drawing: The case of the pension system reform in Mexico - Figueras Zanabria, Víctor Manuel; Culebro Moreno, Jorge Enrique (Universidad Icesi, 2012)
The article’s objective is to analyze the development and evolution of the Mexican pension reform not only as such but also of two main bodies: on the one hand, the regulator (the National Saving for Retirement) and the other, from the pension fund manager designed as a public-private partnership (PPP Manager Retirement Funds, Afore XXI). This article finds firstly, the existence of a horizontal degree of specialization and a potential lack of accountability and transparency in organizations responsible for regulating the pension system, and secondly that the presence of values that may compete in public officials in developing their roles have affected the development of a new pension system in Mexico and the performance of the regulator.

El objetivo del artículo consiste en estudiar la reforma en el sistema de pensiones en México, en particular, el desarrollo y evolución de la reforma de dos principales organismos, por un lado la agencia reguladora y por el otro de la administradora de fondos de pensiones diseñada como una asociación público-privada PPP. Los resultados son, la existencia de un grado de especialización horizontal y una potencial falta de rendición de cuentas y transparencia en las organizaciones encargadas de regular el sistema de pensiones, así como la presencia de valores de que pueden entrar en competencia en los funcionarios públicos en el desarrollo de sus funciones afectando el desarrollo de un nuevos sistema de pensiones y el desempeño del organismo regulador.
Transferencia de políticas y construcción de lecciones. El caso de la reforma al sistema de pensiones en México
Keywords: FACULTAD DE CIENCIAS ADMINISTRATIVAS Y ECONÓMICAS; PRODUCCIÓN INTELECTUAL REGISTRADA - UNIVERSIDAD ICESI; TRANSFERENCIA DE POLÍTICAS PÚBLICAS; SISTEMA PENSIONAL; REFORMAS ADMINISTRATIVAS; POLICY TRANSFER; PENSION SYSTEM; ADMINISTRATIVE REFORM; REGULATION